Stock market development and economic growth in sri lanka: evidence from colombo stock exchange (cse) - Thigashan, S.; Anandasayanan, S. (University of Jaffna, 2017)
Stock market plays vital role in economic growth of any country. The objective of this study is to investigate the impact of stock market development on economic growth in Sri Lanka evidence from listed companies in Colombo stock exchange (CSE) during the period of 2001 to 2015. The hypotheses are examined with help of person’s correlation and regression analysis. This study consists of three measures of stock market development namely stock market capitalization ratio to proxy market size, stock value traded ratio and stock traded turnover ratio to proxy market liquidity, control variable as inflation. GDP growth rate and GNI growth rate are used as a proxy for economic growth. Data were collected from the annual reports companies listed on CSE and central bank of Sri Lanka. Statistical packages for social science (SPSS) was used to analyzes the data and investigate the impact of in dependent variables and independent variable. Based on the multiple regression analysis findings revealed that stock market development significantly impact on economic growth Sri Lanka other than stock value traded ratio and inflation because stock value traded ratio and inflation has insignificant impact on GDP growth rate and GNI growth rate. The results of this study support that the stock market performance plays an important role in economic growth in Sri Lanka. Outcome of the study will useful to the academicians, practitioners, policy markers and investors for making suitable policy formulations for the companies.
Keywords: Stock market development; Economic growth; GDP; GNI